(untitled) (Research, Society and Development, 2020)
The objective of this study is to investigate the self-regulated behavior in the routine of students of the Degree in Biological Sciences of the Federal Institute of Pará - Campus Abaetetuba. It used as a theoretical contribution the Social Cognitive Theory, specifically the Self-Regulation of Learning (SRL), providing students who are authors of their own learning with cognitive processes that allow mastery over their behavior. The study is a qualitative type, as it considers the way the students interpret and give meaning to the development of the phases of SRL. 5 students were interviewed, 2 women and 3 men, aged between 19 and 32 years old, of the 3rd semester of the course, using two instruments for data collection, the sociodemographic questionnaire and the collective interview, whose script was prepared based on the Academic Self-Regulation Scale – ASRS. The speeches of the participants were analyzed using the NVIVO 10 software, using frequency techniques. The results showed that students self-regulate their learning for a good academic performance, however they encounter several difficulties that often discourage them. In this sense, the present work also sought to suggest strategies for strengthening SRL in the course in question.